A new parapithecine (Primates: Anthropoidea) from the early Oligocene of Libya supports parallel evolution of large body size among parapithecids. Issue 153 (April 2021) - Mattingly, Spencer G.; Beard, K. Christopher; Coster, Pauline M.C.; Salem, Mustafa J.; Chaimanee, Yaowalak; Jaeger, Jean-Jacques
Abstract: Parapithecines are an extinct subfamily of stem anthropoid primates previously known only from the Jebel Qatrani Formation in Egypt. Here, we describe isolated teeth pertaining to Simonsius harujensis sp. nov., a relatively small-bodied parapithecine from strata near Zallah Oasis in the Sirt Basin of central Libya that is estimated to date to ∼31 Ma on the basis of mammalian biostratigraphy. The dental morphology of S. harujensis sp. nov. is generally intermediate between that of the closely related parapithecines Parapithecus fraasi and Simonsius grangeri, highlighting some of the anatomical features distinguishing the latter taxa and providing further support for their generic separation. A phylogenetic analysis using parsimony methods was performed on a character-taxon matrix incorporating data from the new Libyan parapithecine, virtually all other parapithecids and the proteopithecid Proteopithecus sylviae . Results of this analysis suggest that parapithecids comprise a basal clade consisting of three species of Biretia and a more derived clade including Parapithecinae ( Parapithecus and Simonsius ) and Qatraniinae ( Qatrania, Ucayalipithecus, and Apidium ). Body mass estimates for parapithecids were calculated on the basis of regression equations generated to predict body mass from the occlusal area of upper and lower cheek teeth in extant anthropoids. The relatively small body mass of S. harujensis sp. nov. and its reconstructed phylogenetic position as the sister group of S. grangeri, which is the largest known parapithecid, support the convergent acquisition of body mass larger than 500 g among multiple clades of early Oligocene African anthropoids. The new Libyan parapithecine augments previously reported evidence supporting a substantial degree of faunal provincialism across northern Africa/Arabia during the early Oligocene.